2008
DOI: 10.1088/0953-8984/20/11/114109
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic investigations of ternary liquid alloys

Abstract: A review of different methods for determining thermodynamic quantities is given. The electromotive force (EMF) method with a liquid and solid electrolyte, the calorimetric and differential scanning calorimetry (DSC) methods, and vapour pressure experiments like the isopiestic and Knudsen effusion methods are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Some authors even did some comparison for different methods and based on which they had confirmed the correction of our new model. [20][21][22][23][24][25][26][27][28][29] Besides we have also considered the calculation in a miscibility area. [30][31][32][33] The above phenomenological model deals with various kinds of properties for solution in a whole concentration range.…”
Section: Calculation Of Physicochemical Properties Of Meltsmentioning
confidence: 99%
“…Some authors even did some comparison for different methods and based on which they had confirmed the correction of our new model. [20][21][22][23][24][25][26][27][28][29] Besides we have also considered the calculation in a miscibility area. [30][31][32][33] The above phenomenological model deals with various kinds of properties for solution in a whole concentration range.…”
Section: Calculation Of Physicochemical Properties Of Meltsmentioning
confidence: 99%
“…Recently interest has been found to investigate the thermodynamical properties of liquid binary and ternary alloys [1][2][3][4][5][6][7][8][9][10][11][12]. A technique based on the Gibbs-Bogoliubov (GB) inequality is well established and very effectively used in past [13][14][15][16][17][18][19] to investigate the thermodynamical properties of liquid binary alloys using pseudopotential theory.…”
Section: Introductionmentioning
confidence: 99%
“…A technique based on the Gibbs-Bogoliubov (GB) inequality is well established and very effectively used in past [13][14][15][16][17][18][19] to investigate the thermodynamical properties of liquid binary alloys using pseudopotential theory. In such type of studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], it is found that thermodynamical properties of liquid binary alloys are sensitive to the form of the model potential used, structural part of the energy, form of the local field correction function and volume of the mixing.…”
Section: Introductionmentioning
confidence: 99%